Rasch Model Analysis: Development of Literacy Numeracy Assessment Instrument of Electromagnetic Induction - Nurul Apriani Susanti; Sarwi Sarwi; Mahardika Prasetya Aji (Physics Communication, 2023)
This research aimed to describe the validity of a numeracy literacy assessment instrument of electromagnetic induction based on minimum capability assessment (MCA) which was develop using Rasch model analysis assisted by Winstep software. The research employed the research and development design with a modified Mardapi model. The instrument was constructed by developing fifteen questions. The analysis of the instrument was utilized to measure the construct and item validity, reliability, item difficulty level, and item discriminatory. This research involved 32 participants in the small-scale test and 206 participants in the large-scale trial. The test result showed that the fifteen questions were suitable to use because it has values that meet the criteria for all measurement variables both on small scale and large-scale tests and could be assess students' numeracy literacy skills.